On the geodetic datums in Sri Lanka - Abeyratne, P.; Featherstone, Will; Tantrigoda, D. (Maney Publishing, 2010)
The geodetic datums in Sri Lanka (formerly Ceylon) for latitude and longitude, height and gravity are described and discussed, because this information is not available in the open literature. It is recommended that most of these datums require some upgrading.